Habilidades blandas y su influencia en el desempeño laboral de los servidores públicos de la EMMAP-EP parroquia “Ángel Pedro Giler” - Campozano Pinto, Elba Monserrate (2024)
The research was carried out with the objective of analyzing the soft skills of the public servants of the EMMAP-EP “Ángel Pedro Giler” Parish to determine their influence on job performance, for which three phases were developed which responded to each of the specific objectives, firstly, an extensive bibliographic review was carried out on the state of the art of the study variables and an analysis regarding the legal and regulatory basis according to the research, then to support the second one in this phase, a questionnaire of questions was designed for the interviews addressed to the General Manager and Head of Human Talent and surveys that were developed using the servqual model and Likert scale which served to measure the level of satisfaction of the collaborators, finally an improvement plan designed using the 5w+1h matrix was presented, detailing and proposing solutions to the different problems detected in the company. In general, it was found that soft skills have great relevance in job performance since they allow public servants to have a better work environment, adapt to changes, work as a team, effective communication to interact with other people, possess skills, knowledge and attitudes to perform effectively in the workplace and be ready to resolve conflicts peacefully.